Pela medida das coisas: seres humanos, animais e justiça social - Fortes, Renata de Mattos (Universidade do Vale do Rio do Sinos, 2009)
This paper aims to show that the national legislation, since 1924, has animal protection legal rules which constitutes animal rights, what means rules that against human interests, and this idea was reinforced since the Federal Constitution of 1988, which providing a democratic order for Brazil, supported the right to life. In order to support the second goal proposed, the theory of focus on capacities by Martha Nussbaum will be presented, where the issues that involves animals, in our culture, would start to be considered as social justice issues, facing the fact that animals have abilities that make them able to evolute and make accomplishments in their own lives.
Keywords: Constituição Federal do Brasil; direitos animais; enfoque das capacidades; animais; animals rights; Brazil Federal Constitution; focus on capacities; animals; Ciências Sociais Aplicadas